Effects of low-to-moderate ethanol consumption on colonic growth and gene expression in young adult and middle-aged male rats - Wells, Nicole; Quigley, Jacqueline; Pascua, Jeremy; Pinkowski, Natalie; Almaiman, Lama; Brasser, Susan M.; Hong, Mee Young (PloS one, 2020)
Excessive alcohol consumption is a risk factor associated with colorectal cancer; however, some epidemiological studies have reported that moderate alcohol consumption may not contribute additional risk or may provide a protective effect reducing colorectal cancer risk. Prior research highlights the importance of proliferation, differentiation, and apoptosis as parameters to consider when evaluating colonic cell growth and tumorigenesis. The present study investigated whether chronic low-to-moderate ethanol consumption altered these parameters of colonic cell growth and expression of related genes. Twenty-four nondeprived young adult (109 days old) and 24 nondeprived middle-aged (420 days old) Wistar rats were randomly assigned to an ethanol-exposed or a water control group ( n = 12/group). The ethanol group was provided voluntary access to a 20% v/v ethanol solution on alternate days for 13 weeks. Colon tissues were collected for quantitative immunohistochemical analyses of cell proliferation, differentiation and apoptosis using Ki-67, goblet cell and TUNEL, respectively. Gene expression of cyclin D1 ( Ccnd1 ), Cdk2 , Cdk4 , p21 waf1/cip1 ( Cdkn1a ), E-cadherin ( Cdh1 ) and p53 were determined by quantitative real-time polymerase chain reaction in colonic scraped mucosa. Ethanol treatment resulted in a lower cell proliferation index and proliferative zone, and lower Cdk2 expression in both age groups, as well as trends toward lower Ccnd1 and higher Cdkn1a expression. Cell differentiation was modestly but significantly reduced by ethanol treatment only in older animals. Overall, older rats showed decreases in apoptosis and gene expression of Cdk4 , Cdh1 , and p53 compared to younger rats, but there was no observed effect of ethanol exposure on these measures. These findings suggest that low-to-moderate ethanol consumption improves at least one notable parameter in colonic tumorigenesis (cell proliferation) and associated gene expression regardless of age, however, selectively decreased cell differentiation among older subjects.